Inclusive Digital Narratives: Analyzing Toxicity, Topics, and Social Networks in Indigenous Documentaries Content Reviews - Singgalen, Yerik Afrianto (Institute of Computer Science (IOCS), 2024)
The research delves into the livelihood and coping strategies of indigenous communities in the digital era, focusing on the analysis of digital content. Utilizing the CRISP-DM framework, the study investigates toxicity scores, topics, and social networks within digital content, particularly examining video documentaries portraying indigenous communities' ways of life. Through data understanding, scraping, and modeling, the research unveils insights into the toxicity levels of online discussions and identifies topics resonating with viewers. The findings underscore the significance of preserving indigenous cultures, promoting community well-being, and fostering inclusive digital content. Moreover, the analysis reveals 8,776 actors and 498 edges within social networks, with an average degree of connectivity of 0.051 and an average weighted degree of 0.057. Notably, the toxicity analysis shows relatively low toxicity levels, with a toxicity score of 0.04992 and severe toxicity at 0.00609. The study concludes by recommending strategies to enhance the quality and sensitivity of digital content, contributing to broader societal understanding and appreciation of indigenous communities.